Jnk2 effects on tumor development, genetic instability and replicative stress in an oncogene-driven mouse mammary tumor model. - Peila Chen; Jamye F O'Neal; Nancy D Ebelt; Michael A Cantrell; Shreya Mitra; Azadeh Nasrazadani; Tracy L Vandenbroek; Lynn E Heasley; Carla L Van Den Berg (PLoS ONE, 2010)
Oncogenes induce cell proliferation leading to replicative stress, DNA damage and genomic instability. A wide variety of cellular stresses activate c-Jun N-terminal kinase (JNK) proteins, but few studies have directly addressed the roles of JNK isoforms in tumor development. Herein, we show that jnk2 knockout mice expressing the Polyoma Middle T Antigen transgene developed mammary tumors earlier and experienced higher tumor multiplicity compared to jnk2 wildtype mice. Lack of jnk2 expression was associated with higher tumor aneuploidy and reduced DNA damage response, as marked by fewer pH2AX and 53BP1 nuclear foci. Comparative genomic hybridization further confirmed increased genomic instability in PyV MT/jnk2-/- tumors. In vitro, PyV MT/jnk2-/- cells underwent replicative stress and cell death as evidenced by lower BrdU incorporation, and sustained chromatin licensing and DNA replication factor 1 (CDT1) and p21(Waf1) protein expression, and phosphorylation of Chk1 after serum stimulation, but this response was not associated with phosphorylation of p53 Ser15. Adenoviral overexpression of CDT1 led to similar differences between jnk2 wildtype and knockout cells. In normal mammary cells undergoing UV induced single stranded DNA breaks, JNK2 localized to RPA (Replication Protein A) coated strands indicating that JNK2 responds early to single stranded DNA damage and is critical for subsequent recruitment of DNA repair proteins. Together, these data support that JNK2 prevents replicative stress by coordinating cell cycle progression and DNA damage repair mechanisms.